Optimalisasi Strategi Pemasaran Kerupuk Bawang UMKM MJT di Desa Siwalan Nganjuk Melalui Pendekatan STP dan Marketing Mix - Ika Puspitasari Dyah Rahmadhani; Tiara Ayu Nugraha Putri (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Micro, Small, and Medium Enterprises (MSMEs) are vital to the Indonesian economy, yet they often face challenges such as limited capital, low-quality human resources, weak marketing strategies, and lack of product innovation. MJT MSME is a small business that produces onion crackers in Siwalan Village, Sawahan Subdistrict, Nganjuk Regency. MSMEs in this area experienced a 6% increase compared to 2023. With increasing competition in the cracker industry, these businesses must adapt to remain competitive and sustainable. This study aims to analyze and develop an optimal marketing strategy for the MJT onion cracker MSME in Siwalan Village by integrating the STP framework and the 4P marketing mix, tailored to the current market conditions. The research method used is descriptive qualitative method. The research was conducted in February 2025 and located in MJT MSMEs, Nganjuk with a total of 15 respondents. The research location was selected by purposive sampling to ensure relevance to the research objectives. The data collection methods used were semi-structured interviews, questionnaires, direct observation, and document studies. This research uses a qualitative descriptive approach using two main analytical frameworks: STP (segmenting, targeting, positioning) and the 4P marketing mix (product, price, place, promotion). The results showed that the development strategy by utilizing appropriate technology can be used to maintain the sustainability of onion cracker products. The application of appropriate technology is given as a solution to sustain production in the face of seasonal obstacles and spikes in product demand as well as an adaptive marketing strategy for businesses in facing an increasingly competitive market.